2013
DOI: 10.1126/science.1237013
|View full text |Cite
|
Sign up to set email alerts
|

GPR15-Mediated Homing Controls Immune Homeostasis in the Large Intestine Mucosa

Abstract: Lymphocyte homing, which contributes to inflammation, has been studied extensively in the small intestine, but there is little known about homing to the large intestine, the site most commonly affected in inflammatory bowel disease. GPR15, an orphan G-protein coupled receptor, controlled the specific homing of T cells, particularly FOXP3+ regulatory T cells (Tregs), to the large intestine lamina propria (LILP). GPR15 expression was modulated by gut microbiota and transforming growth factor-β1, but not by retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
251
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(285 citation statements)
references
References 37 publications
12
251
1
2
Order By: Relevance
“…Interestingly, Foxp3 þ RORgt þ T cells also showed increased expression of Gpr15 and Ffar2, the two receptors with fundamental roles especially in colonic Treg homeostasis. 28,29 To directly assess the tissue-homing capacity of Foxp3 þ RORgt þ T cells, we performed short-term homing assays using adoptive transfer of radiolabeled T cells into wild-type recipient mice. 30 Although Foxp3 þ RORgt þ T cells showed a slight tendency toward enhanced homing into mucosal tissues, overall the migration behavior was comparable to Foxp3 þ Tregs (Supplementary Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Foxp3 þ RORgt þ T cells also showed increased expression of Gpr15 and Ffar2, the two receptors with fundamental roles especially in colonic Treg homeostasis. 28,29 To directly assess the tissue-homing capacity of Foxp3 þ RORgt þ T cells, we performed short-term homing assays using adoptive transfer of radiolabeled T cells into wild-type recipient mice. 30 Although Foxp3 þ RORgt þ T cells showed a slight tendency toward enhanced homing into mucosal tissues, overall the migration behavior was comparable to Foxp3 þ Tregs (Supplementary Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Its expression correlates loosely but significantly with that of P-selectin binding. G protein-coupled receptor 15 (GPR15), which is implicated in T cell homing to the colon and potentially to the skin (47)(48)(49), is also expressed by subsets of PBs within each disease-associated class, without a clear enrichment in or restriction to cells targeted to intestinal sites (Y. Seong and N.H. Lazarus, unpublished observations). As proposed for CXCR3, it may regulate microenvironmental localization or inflammatory insult-selective recruitment of PBs.…”
Section: Discussionmentioning
confidence: 99%
“…GPR15 is an orphan G protein-linked receptor and an HIV coreceptor with homology to other known lymphocyte-trafficking receptors, but its ligand is unknown so far (15,16). Interestingly, it was shown that in mice the expression of GPR15 and its function as a migration molecule is restricted to Tregs, whereas in humans GPR15 was shown to be expressed on Tregs, Teffs, and memory T cells (12,13). No difference in the suppressive capacity in vitro and in vivo was observed for murine GPR15 + and GPR15 -CD4 + Tregs (12).…”
Section: Introductionmentioning
confidence: 99%
“…Although the trafficking of T cells from the circulation into the small intestine has been well described and is associated with the expression of α4β7 and CCR9, the trafficking of T cells into the colon was only recently discovered to be dependent on the expression of G protein-coupled receptor 15 (GPR15) (8)(9)(10)(11)(12)(13)(14). GPR15 is an orphan G protein-linked receptor and an HIV coreceptor with homology to other known lymphocyte-trafficking receptors, but its ligand is unknown so far (15,16).…”
Section: Introductionmentioning
confidence: 99%